Reproductive Health Counseling for Gilt and Sow - Feribertus Rinca, Korbinianus; Ingrida Velisia Amul; Kosmas Ardino; Damianus Soni Hegam (International Journal of Community Service Learning, 2024)
Heifer and sow pig farms in Golo Wua village are experiencing problems in managing reproductive health. To overcome this problem, the community service team from the Indonesian Catholic University Santu Paulus Ruteng conducted outreach using the lecture method directly for breeders using qualitative research. Data collection methods were carried out through observation, interviews, and documentation. The target of this extension activity is pig farmers, especially those raising heifers and sows. This counseling was carried out at the Golo Wua village hall and was attended by 33 breeders. The results of the outreach activities showed that participants' knowledge regarding reproductive health management for heifers and sows increased after attending the outreach. Therefore, counseling is the right method to increase pig breeders' understanding in overcoming problems related to the reproductive health of heifers and sows. The implications of this research are improving animal reproductive health and optimizing productivity. The main objective of this research is to increase farmer awareness about the importance of reproductive health in gilts and sows. This involves education about the reproductive cycle, signs of good reproductive health, and the impact of management practices on animal reproductive health.